1990
DOI: 10.1007/bf00294228
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neurons in the frontal cortex in AIDS brains

Abstract: Neurons of Area 11 in the fronto-orbital cortex of 18 unselected AIDS brains are analyzed by means of stereology. Neurological abnormalities including dementing symptoms were described in eight patients. Neuropathology diagnosed human immunodeficiency virus (HIV)-specific changes in four, and diffuse poliodystrophy in eight brains. The majority (71.4%) of these brains was immunoreactive for HIV antigens when tested by immunocytochemistry. A significant loss of neurons is found as compared to normal controls. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(105 citation statements)
references
References 10 publications
5
99
1
Order By: Relevance
“…Previous studies have documented neuronal loss in both demented and nondemented AIDS patients (19,20). As many as 50% of AIDS patients with dementia do not have histopathologic evidence of HIV-1 encephalitis, particularly patients with milder symptoms (4, 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented neuronal loss in both demented and nondemented AIDS patients (19,20). As many as 50% of AIDS patients with dementia do not have histopathologic evidence of HIV-1 encephalitis, particularly patients with milder symptoms (4, 7).…”
Section: Discussionmentioning
confidence: 99%
“…The neuropathology of HIV-1 infection includes brain atrophy, demyelination, reactive astrocytosis, microglial nodules, multinucleated giant cells, and evidence of abnormal blood-brain-barrier permeability (3)(4)(5)(14)(15)(16)(17)(18). Neuronal loss, dendritic pathology, and decreased synaptic density have also been documented (19)(20)(21)(22). Affected brain regions include the basal ganglia, subcortical white matter, and cerebral cortex (1,4,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The development of neurological disease in individuals infected with human immunode®ciency virus (HIV) is the culmination of a long history of viral interactions with the brain which slowly kill selected cortical and subcortical neurons (Wiley et al, 1991;Ketzler et al, 1990;Weis et al, 1993;Gray et al, 1991). Data from both human and animal studies suggest that the neural disease, is progressive and that it may begin in the asymptomatic stage, long before the development of AIDS (Lendhardt et al, 1988;Elovaara et al, 1990;Meeker et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Manifestations of ADC are progressive cognitive, motor, and behavioral dysfunctions that have been linked to the persistence of HIV-1 infections in the CNS and are mainly found in CD4-positive (CD4+) microglial cells and circulating macrophages (Budka, 1991;Fauci, 1988;Jordan et al, 1991;Ketzler et al, 1990;Liu et al, 1990;Maddon et al, 1986;McArthur, 1987;Merrill and Chen, 1991;Price et al, 1988). However, in the absence of CD4 molecules on the cell membrane of the majority of brain cells and in the light of the paucity of direct evidence for HIV infection of neurons and glial cells it has been suggested that the HIV-associated degenerative neurological abnormalities are the result of indirect mechanisms mediated by soluble factors of viral or cellular origin (Brenneman et a/., 1988;Dreyer et al, 1990;Giulian et al, 1990;Kaiser et al, 1990;Pulliam et al, 1991;Wahl et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%